Sane Fragility - Madness meets critical whiteness. - Glück, Rosa Kato (Disability & Society, 2025)
Sanism is an oppressive system which discriminates against people who are labelled or identify as Mad. This article offers tools to describe the structure, operating modes and dynamics of sanism. It thereby refers to the concept of white fragility. I observe sanism on three levels: The structural frame, aspects of individual interactions and issues of intrapersonal processes. Sane fragility occurs on each level. It manifests in the fragile state of sanity as a whole, the lack of stamina or strength a lot of sane people display when confronted with Mad people and in madphobia - the fear of becoming Mad oneself and therefore othering Mad people. I conclude that sanism is an overlooked type of oppression with multilayered dynamics and intersections with fatal consequences. I am a Mad, Queer person and this article contains Mad storytelling along with insights gathered from Black feminism, Queer Theory and Mad Studies. Points of interest: Sane Fragility I am a person with mental health problems and besides living with those issues, I also have to struggle because of discrimination against me as a Mad person. This discrimination is called sanism and I want to observe it, in order to understand it, so we can be able to fight it. For this purpose, I lean into different theories to define the term 'sane fragility'. Sane fragility means, that people who do not struggle with mental health issues are often overwhelmed and not able to cope, if other people are in crisis, while Mad people developed a strenght to deal with it. This sort of stress leads to sane people avoiding and discriminating Mad people, because they are too fragile to bear with us.